(untitled) (Management and Connections Journal, 2025)
The transformations in contemporary society, driven by the evolution of the internet and technological innovations, have redefined the purchasing process. Currently, transactions take place remotely and swiftly through digital e-commerce platforms, with e-marketplaces emerging as primary channels for research and acquisition. Globally, countries seek to streamline government procurements, adopting innovative practices to promote speed, efficiency, transparency, competition, and cost reduction. Through a systematic review, this research explored the state of the art in academia on the subject. Only 14 studies were identified in databases such as Scopus, SciELO, Google Scholar, Web of Science, and BDTD. The results highlight the recent focus on the topic, with scientific journals being the primary source of publications, predominantly in countries that have already implemented e-marketplaces in their procurements.